Epigenetic clock and methylation studies in vervet monkeys - Anna J. Jasinska; Amin Haghani; Joseph A. Zoller; Caesar Z. Li; Adriana Arneson; Jason Ernst; Kylie Kavanagh; Matthew J. Jorgensen; Julie A. Mattison; Kevin Wojta; Oi-Wa Choi; Joseph DeYoung; et al. (GeroScience, 2022)
DNA methylation-based biomarkers of aging have been developed for many mammals but not yet for the vervet monkey ( Chlorocebus sabaeus ), which is a valuable non-human primate model for biomedical studies. We generated novel DNA methylation data from vervet cerebral cortex, blood, and liver using highly conserved mammalian CpGs represented on a custom array (HorvathMammalMethylChip40). We present six DNA methylation-based estimators of age: vervet multi-tissue epigenetic clock and tissue-specific clocks for brain cortex, blood, and liver. In addition, we developed two dual species clocks (human-vervet clocks) for measuring chronological age and relative age, respectively. Relative age was defined as ratio of chronological age to maximum lifespan to address the species differences in maximum lifespan. The high accuracy of the human-vervet clocks demonstrates that epigenetic aging processes are evolutionary conserved in primates. When applying these vervet clocks to tissue samples from another primate species, rhesus macaque, we observed high age correlations but strong offsets. We characterized CpGs that correlate significantly with age in the vervet. CpG probes that gain methylation with age across tissues were located near the targets of Polycomb proteins SUZ12 and EED and genes possessing the trimethylated H3K27 mark in their promoters. The epigenetic clocks are expected to be useful for anti-aging studies in vervets.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

A genetic linkage map of the vervet monkey (Chlorocebus aethiops sabaeus) - Anna J. Jasinska; Susan Service; Matthew Levinson; Erin Slaten; Oliver Lee; Eric Sobel; Lynn A. Fairbanks; Julia N. Bailey; Matthew J. Jorgensen; Sherry E. Breidenthal; Ken Dewar; Thomas J. Hudson; et al. (Mammalian Genome, 2007)

Analysis of segmental duplications reveals a distinct pattern of continuation-of-synteny between human and mouse genomes - Michael R. Mehan; Maricel Almonte; Erin Slaten; Nelson B. Freimer; P. Nagesh Rao; Roel A. Ophoff (Human Genetics, 2007)

Significant linkage to airway responsiveness on chromosome 12q24 in families of children with asthma in Costa Rica - Juan C. Celedón; Manuel E. Soto-Quiros; Lydiana Avila; Stephen L. Lake; Catherine Liang; Eduardo Fournier; Mitzi Spesny; Craig P. Hersh; Jody S. Sylvia; Thomas J. Hudson; Andrei Verner; Barbara J. Klanderman; et al. (Human Genetics, 2006)

Benign recurrent intrahepatic cholestasis (BRIC): evidence of genetic heterogeneity and delimitation of the BRIC locus to a 7-cM interval between D18S69 and D18S64 - Richard J. Sinke; Victoria E. H. Carlton; Jenneke A. Juijn; Tammo Delhaas; Gerard P. Berge Henegouwen; Jan van Hattum; Klaus M. Keller; Maarten Sinaasappel; Charles M. A. Bijleveld; Hans-Kristian Ploos van Amstel; Peter L. Pearson; Nelson B. Freimer; et al. (Human Genetics, 1997)